Enhancement Mechanical Properties of Simalambuo Wood (Loppophetalum spp) Delignified using NaOH in The Thermomechanical Densification Method - Nur Azizah; Febri Sindika; Andriayani Andriayani; Saharman Gea (Jurnal Akademika Kimia, 2022)
One of the problems with fast-growing wood is the low density, which causes poor mechanical properties, so a densification process is carried out to increase the wood's density, surface hardness, and strength. In this study, the delignification process using NaOH was carried out at variations of 12.24, and 48 hours and then continued with the thermomechanical densification process. This study decreased lignin content in delignification simalambuo wood from 30% to 4%. The value of the Modulus of Rupture, Modulus of elasticity, and surface hardness increases with increasing immersion time during the delignification process. The highest values of Modulus of Rupture, Modulus of elasticity, and surface hardness were obtained by simalambuo wood soaked for 48 hours, namely, 2828.23 kg/cm2, 97.47 kg/cm2, and 256.73 kg/cm2.